Livestock production in central Mali: Effects of climatic variables on the period of birth and on litter size in traditionally managed goats and sheep - Wilson, R.T.; Sayers, A.R. (1987)
Discusses the effets of maximum and minimum temperature, maximum and minimum relative humidity, rainfall and daylength on the timing of parturition and on litter size in traditionally managed goats and sheep in central Mali.